Reliably straining suspended van der Waals heterostructures - Daniele Nazzari; Jakob Genser; Masiar Sistani; Maximilian G. Bartmann; Xavier Cartoixà; Riccardo Rurali; Walter M. Weber; Alois Lugstein (APL Materials, 2023)
2D materials provide a rapidly expanding platform for the observation of novel physical phenomena and for the realization of cutting-edge optoelectronic devices. In addition to their peculiar individual characteristics, 2D materials can be stacked into complex van der Waals heterostructures, greatly expanding their potential. Moreover, thanks to their excellent stretchability, strain can be used as a powerful control knob to tune or boost many of their properties. Here, we present a novel method to reliably and repeatedly apply a high uniaxial tensile strain to suspended van der Waals heterostructures. The reported device is engineered starting from a silicon-on-insulator substrate, allowing for the realization of suspended silicon beams that can amplify the applied strain. The strain module functionality is demonstrated using single- and double-layer graphene layers stacked with a multilayered hexagonal boron nitride flake. The heterostructures can be uniaxially strained, respectively, up to ∼1.2% and ∼1.8%.